2013
DOI: 10.1095/biolreprod.112.106773
|View full text |Cite
|
Sign up to set email alerts
|

Mouse HORMAD1 Is a Meiosis I Checkpoint Protein That Modulates DNA Double-Strand Break Repair During Female Meiosis1

Abstract: Oocytes in embryonic ovaries enter meiosis I and arrest in the diplonema stage. Perturbations in meiosis I, such as abnormal double-strand break (DSB) formation and repair, adversely affect oocyte survival. We previously discovered that HORMAD1 is a critical component of the synaptonemal complex but not essential for oocyte survival. No significant differences were observed in the number of primordial, primary, secondary, and developing follicles between wild-type and Hormad1(−/−)newborn, 8-day, and 80-day ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…For example, HORMA domain-containing 1 (Hormad1) is a major pachytene checkpoint, and our previous work revealed that Hormad1-deficient oocytes have unsynapsed chromosomes and lack pachynema, yet have a normal number of primordial follicles with normal oogenesis and folliculogenesis (31,32). Hormad1 deficiency does not affect oocyte differentiation (33), nor does it perturb the expression of SOHLH1 (Supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…For example, HORMA domain-containing 1 (Hormad1) is a major pachytene checkpoint, and our previous work revealed that Hormad1-deficient oocytes have unsynapsed chromosomes and lack pachynema, yet have a normal number of primordial follicles with normal oogenesis and folliculogenesis (31,32). Hormad1 deficiency does not affect oocyte differentiation (33), nor does it perturb the expression of SOHLH1 (Supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…The MCM9 interactome obtained by tandem affinity purification and mass spectrometry analysis ( Figures 1A, 1B, and S1) revealed some new MCM9 partners implicated in meiosis, replication, and repair, such as the meiosis checkpoint protein HORMAD1, which modulates DNA double-strand break repair during female meiosis (Shin et al, 2013), and the Replication Factor C (RFC) family, which is implicated in DNA replication and repair, including MMR. Nevertheless, our results show that that the more significant MCM9 interactors are MCM8 (Lutzmann et al, 2012;Nishimura et al, 2012;Park et al, 2013) and several proteins with established roles in the MMR process.…”
Section: Discussionmentioning
confidence: 99%
“…They form the platform for the binding and phosphorylation of HORMAD proteins, which form a key part of the chromosomal environment for the MCN in many organisms (Xu et al 1997;Martinez-Perez and Villeneuve 2005;Carballo et al 2008;Lin et al 2010;Shin et al 2010Shin et al , 2013Daniel et al 2011;Kogo et al 2012a,b;Wojtasz et al 2012;Cheng et al 2013). In addition, chromosome axis components also interact directly with components of MCN.…”
Section: The Context Mattersmentioning
confidence: 99%
“…It is possible that the presence of HORMADs on unsynapsed chromosomes is itself the signal activating the MCN. In mouse, HORMAD1 has multiple roles in meiotic prophase (Shin et al 2010(Shin et al , 2013Daniel et al 2011), whereas HORMAD2 is selectively required for SPO11-independent spreading of g-H2AFX and MSUC/MSCI (Wojtasz et al 2012). Because HORMAD2 directly binds to HORMAD1 (Wojtasz et al 2012), an intriguing possibility is that HORMAD1/2 colocalization creates a SPO11-independent signal to activate the MCN.…”
Section: Signal Generationmentioning
confidence: 99%